Numerical simulation of unsteady airflow organization and cold island effect in air source heat pump unit - Jiashuo Zhou; Ronghua Wu; Hao Yu; Jiyou Lin; Hao Zhan; Shunjie Liu; Zhibin Wang (Case Studies in Thermal Engineering)
During winter heating operations, the cold air discharged by air source heat pump (ASHP) units accumulates around them, resulting in a cold island effect that decreases the system's heating capacity. This paper presents an unsteady computational fluid dynamics (CFD) simulation model to investigate the airflow organization of a single ASHP unit. It examines how environmental temperature, wind speed, and air volume influence airflow patterns and analyzes the effects on the coefficient of performance (COP). The findings reveal a maximum relative error of 14.5 % between the simulated and experimental COP results. The airflow organization progresses through three stages: viscosity-dominated, accelerated suction, and periodic ejection. The cold island effect can lead to a 3.28 % drop in baseline COP compared to the theoretical COP, with decreases reaching 4.17 % at an ambient temperature of 15 °C and 6.54 % at an air volume of 13527 m3/h. The research findings of this study provide a basis for the quantitative engineering analysis of performance degradation in single-unit air-source heat pump systems caused by the cold island effect. Additionally, the introduction of a non-steady-state model offers new insights into the precise characterization of the cold island effect in air-source heat pump units.